Сучасні лінгвістичні погляди на природу і функції іменника як частини мови - Шиманович, Г.М. (Культура народов Причерноморья, 2013)
Стаття присвячена дослідженню іменника, а саме його природи та функцій. Дослідження природи найменування словами різних частин мови э одним з найголовніших положень для уточнення й розвитку теорії номінації. Частини мови неодноразово привертали до себе увагу лінгвістів різних напрямків та шкіл і продовжують досліджуватися в різних аспектах, з різних точок зору сучасних лінгвістичних теорій та підходів. Для сучасних лінгвістичних досліджень є характерним комплексний багатоаспектний аналіз номінативних одиниць, при якому когнітивні параметри вивчаються в тісному зв’язку з параметрами комунікативними. Іменник завжди був у центрі досліджень і був вихідною точкою і підставою для порівняння. У виникненні і розвитку системи частин мови іменнику належить центральне місце, тому що певною мірою всі інші слова можуть бути виведені з предметних і подійних імен. Ключові слова: іменник, частини мови, ономасіологічний підхід, номінативна функція. Статья посвящена исследованию природы и функций имени существительного в системе частей речи в современном английском языке. В работе освещены современные взгляды, подходы и теории в изучении данной части речи, а именно ономасиологический, когнитивный и прототипический подходы, генеративная теория и др. Ключевые слова: имя существительное, части речи, ономасиологический подход, номинативная функция. The article is devoted to profound study of the functions, place and role of Noun in the system of the Modern English language. Different modern linguistic approaches to the category of English Noun are analyzed in this article. The features of the noun within the identificational triad “meaning-form-function” are correspondingly, the following 1) the categorical meaning of substance; 2) the changeable forms of number and case; 3) the substantive functions in the sentence. Noun has got plenty of nominative functions, because it can fulfil almost any syntactical function, denoting Agent, Patient, Instrument etc. Nouns can be used as semantic equivalents of the whole expressions. They can name not only actions, qualities, conditions, but also more complicated notions. Noun has got limited number of morphological categories, such as the category of number, case. The grammatical category of gender is factually absent in Modern English. The noun is the main nominative part of speech, effecting nomination of the fullest value within the framework of the notional division of the lexicon. As a part of speech, the noun is also characterized by a set of formal features determining its specific status in the lexical paradigm of nomination. It has its word-building distinctions. The noun has the power, by way of nomination, to isolate different properties of substances (i.e. direct and oblique qualities, and also actions and states as processual characteristics of substantive phenomena) and present them as corresponding self-dependent substances. This natural and practically unlimited substantivization force establishes the noun as the central nominative lexemic unit of language. Key words: Noun, Part of Speech, onomasiological approach, nominative function.